Development of new method for dispersing nanofillers in polycaprolactone (pcl) nanocomposite - Shamini, Vesaya Kumaran (2014)
The consumption of plastic materials has been increasing and the accumulation of plastic at the end of its life cycle has also increased on the earth. This causes a big waste disposal and pollution problem. Therefore, this motivated many researchers to conduct studies to produce a polymer which is biodegradable and environmental friendly and at the same time has improved properties to produce plastics. Polymer nanocomposites have gained the greatest interest in this issue since few years. Polycaprolactone (PCL) as the polymer and Sodium montmorillonite (Na-MMT) a type of nanoclay as the inorganic nanofiller is used in this study. However, the polymer matrix and the nanoclay surface are not compatible because the inorganic Na-MMT is hydrophilic and PCL is hydrophobic. Thus, the main aim of this study is to develop a new modification method for dispersing the nanofiller into PCL nanocomposite and to fabricate PCL nanocomposite. The surface of Na-MMT was modified from inorganic to organic through surfactant method by reacting Aminopropylisooctyl Polyhedral Oligomeric Silsesquioxane (AP-POSS) surfactant with Na-MMT and the fabrication of PCL nanocomposite was then done through solution intercalation technique with both modified and unmodified nanoclay of different weight percentages. The structure and morphology of pure nanoclay, modified nanoclay (POSS-MMT) and the PCL nanocomposite were characterized by X-ray Diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR) and Field Emission Scanning Electron Microscopy (FESEM). XRD revealed that the d-spacing of the POSS-MMT is increased by 0.64 nm as compared to Na-MMT. FTIR and FESEM results also showed that AP-POSS were well dispersed and intercalated throughout the interlayer space of Na-MMT. An exfoliated structure was also observed for PCL/POSS-MMT nanocomposite. Thermal properties of the nanocomposite were investigated using Differential Scanning Calorimetry (DSC) analysis which showed highest melting and crystallization temperature in PCL/POSS-MMT 5% nanocomposite which is 56.6˚C and 32.7˚C respectively whereas a lower degree of crystallinity for PCL/POSS-MMT nanocomposite as compared to PCL/Na-MMT nanocomposite and Thermogravimetric Analysis (TGA) recorded the highest degradation temperature in PCL/POSS-MMT 1% nanocomposite which is 394.1˚C at 50% weight loss (T50%) but a decrease in degradation temperature when POSS-MMT content is increased. Mechanical properties of the nanocomposite were analysed through tensile testing and the results indicated the highest Young’s Modulus and tensile strength for PCL/POSS-MMT 3% nanocomposite which is 87 MPa and 2.64 MPa respectively while the lowest elongation at break in PCL/POSS-MMT 1% nanocomposite which is 138%. This study affords an efficient modification method to obtain organoclay with larger interlayer d-spacing to enhance the properties of polymer nanocomposite